ANALISIS PENERIMAAN PENGGUNA TERHADAP PEMBELAJARAN MULTIMEDIA PEMROGRAMAN BERORIENTASI OBJEK BERBASIS QR CODE PADA PENDIDIKAN VOKASI DENGAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Dwi Fitria Al Husaeni; Mumu Komaro; Lala Septem Riza; Eka Fitrajaya Rahman; Erna Piantari; Amay Suherman (Universitas Muhammadiyah Surabaya, 2025)
The research objective is to analyze the Technology Acceptance Model (TAM) in measuring QR Code-based object-oriented programming learning multimedia in supporting vocational school students' learning on problem-based object-oriented programming (PBO) material. The TAM model variables used consist of Perceived Usefulness (PU), Perceived Ease of User (PEU), and User Acceptance of IT (UA-IT). The research respondents consisted of 35 students of SMK Negeri 1 Cimahi. The research stages consisted of familiarizing respondents with the use of multimedia, distributing TAM questionnaires, and testing the TAM model using SmartPLS software. The research results show that the average value of the user response questionnaire for QR Code-based PBO learning multimedia is 84.95% in the